The performance of journal bearings with a single axial groove - Claro, José Carlos Pimenta (1990)
A computer program has been developed that can be used in the analysis of steadily loaded journal bearings with a single groove at any location with respect to the load line. The program incorporates Elrod's cavitation algorithm which ensures mass conservation in both the full film and the cavitated regions enabling rupture and reformation boundaries to be located automatically. Computer results are plotted and checked against experimental measurements for the cases of a single axial groove located at the load line and at 90º to the load line. A comparison of results of this method of analysis with the performance predictions of ESDU Item No. 84031 (1984) for bearings with a single axial groove at 90º to the load line is presented.